Involvement in and Views on Social Responsibility of Gauteng Members of the South African Society of Physiotherapy: A Cross-sectional Survey - K Mostert-Wentzel; LJ Masenyetse; N Dinat; A Botha; LD Jonkers; LC Oosthuizen (AOSIS, 2012)
How do physiotherapists in Gauteng Province,who are members of the South African Society of Physiotherapy(SASP), view social responsibility?A cross-sectional survey was conducted after ethics approval.All 1 098 Gauteng members of the SASP were invited via a thirdpartye-mail to reach the a priori minimum sample size of 97. Theweb-based questionnaire was developed from literature, an earlierSASP survey and a position paper of the American Physical TherapyAssociation (APTA). Five experts validated the instrument.The Likert scale scores indicating agreement with indicatorsof social responsibility were totalled to form a composite socialresponsibility score. The chi-square test for independence was used to determine associations between the categorisedcomposite social responsibility score and categorical variables. Mean difference of continuous variables betweenthe categorised core for two groups were tested using the two-sample t-test. All variables with a P-value less than0.05 were included in the logistic regression analysis to investigate predictors of the necessity of social responsibility.The survey was completed by 163 participants. Of the sample, 96.9% viewed social responsibility as important.Subjects agreed most with "advocating for the health needs of society" (74,2%) and the least with "political activism"(6.1%). Compulsory community service positively influenced 74.6%.Most physiotherapists in the study viewed social responsibility as important and were involved in volunteering.There is scope to broaden the understanding among physiotherapists of what social responsibility entails.